(untitled) (Strathmore Law Journal, 2022)
The prevalence of child trafficking and its widespread impunity, whether committed in Nigeria or outside the country, has been firmly condemned by the United Nations and its eradication has been consistently recognised in both regional and international laws. The main aim of the article is to examine how effectively the legal framework on eradication of child trafficking in Nigeria has addressed several incidences of trafficking. Driven primarily by efforts to combat child trafficking, overcome the multiple ensuing challenges, and promote a child-friendly environment, there is an urgent need to re-examine the existing legislation on child trafficking with a view to ascertain the inadequacies in Nigerian trafficking laws. Further, the problematic scenario is relatively attributed to poor regulatory frameworks, and has become imperative to re-examine the legislation in order to curb the emerging challenges in Nigeria. This paper investigates what impedes the eradication of child trafficking in Nigeria, and what measures could overcome such problems. This paper adopts an analytical and qualitative approach and builds its argument on existing literature and a synthesis of the ideas in this body of knowledge. It argues that continued neglect of the inadequacies existing in Nigeria’s legislation on child trafficking portends a clog in the eradication of child trafficking in the country. Nevertheless, this article provides some recommendations to guide policy makers on how child trafficking can be properly eradicated in Nigeria.